In-situ testing of the shear strength of masonry joints – Proposal for a new Simplified testing approach and Comparison to existing techniques. (28th February 2022) - Burton, C.; Vaculik, J.; Griffith, M.C.; Visintin, P.
Highlights: The in-situ brick shove test is experimentally benchmarked against the couplet test. A simpler in-situ 'pull test' is also trialled, loading the brick out-of-plane. For plain bricks, shove and pull tests are slightly conservative relative to couplet. For frogged bricks, both in-situ tests overestimate shear strength relative to couplet - Selection of in-situ approach needs to reflect the intended end-use of test data. Abstract: For other than minor modifications or additions to existing masonry structures, an understanding of the in-situ mechanical properties of the masonry is required. Estimation of shear strength of the masonry bond is often made using the in-plane shove test as it only requires access from one side of the masonry being tested, and is therefore considered to be only mildly invasive. In-situ and laboratory simulations of the shove tests have however shown that a number of site-specific problems can arise. These include: preparation of the test area which can damage the mortar joints resulting in loss of cohesion, imprecise alignment of both the loading system and instrumentation leading to complications with data interpretation, and without an adequately long section of wall to be tested, flexural cracking and lateral displacement of large wall sections. In an attempt to address these issues, in this paper, an alternative in-situ test is proposed. This new ' pull test' measures shear strength by extracting a single brick orthogonally in the wall's out-of-plane direction. A laboratory investigation is performed to compare the two types of in-situ test (shove and pull) using plain and frogged units, as well as lime and cement mortars, and both tests are further benchmarked using the standard laboratory couplet test. It is demonstrated that for regular (rectangular), plain units with weak mortar, the two in-situ tests produce strength measurements that are statistically equivalent, indicating that under this specific scenario the out-of-plane shear strength can be used as a proxy for the in-plane shear strength, and that the pull test could be used as an alternative to the shove test. In addition, the new pull test is shown to perform with demonstrated repeatability, requires minimal instrumentation, and is particularly relevant for design of anchorages under out-of-plane loading.